2021
DOI: 10.1002/jcla.24031
|View full text |Cite
|
Sign up to set email alerts
|

A five‐gene methylation signature predicts overall survival of patients with clear cell renal cell carcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Therefore, research on cancer biomarkers and outcome prediction of pRCC has been a research hotspot recently. Jing et al found that methylation of ve genes (CCNB2, CDKN1C, CTSH, E2F2, and ERMP1) was related to the prognosis of pRCC patients and could become potential targets of methylation-mediated immunotherapy [32]. Dang et al identi ed 15 ferroptosis-linked lncRNAs associated with the prognosis of pRCC patients through TCGA data mining to generate a prognosis-linked risk model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research on cancer biomarkers and outcome prediction of pRCC has been a research hotspot recently. Jing et al found that methylation of ve genes (CCNB2, CDKN1C, CTSH, E2F2, and ERMP1) was related to the prognosis of pRCC patients and could become potential targets of methylation-mediated immunotherapy [32]. Dang et al identi ed 15 ferroptosis-linked lncRNAs associated with the prognosis of pRCC patients through TCGA data mining to generate a prognosis-linked risk model.…”
Section: Discussionmentioning
confidence: 99%